Neuronale Veränderungen bei chronisch-depressiven Patienten während psychoanalytischer Psychotherapie: Funktionelle-Magnetresonanztomographie-Studie mit einem Bindungsparadigma = Neuronal changes in chronic depressed patients during psychoanalytic psychotherapy : functional magnetic resonance imaging study with an attachment paradigm - Buchheim, Anna; Cierpka, Manfred (Psychotherapeut, 2012)
Neuroimaging studies of depression have examined the effect of short-term, interpersonal or cognitive-behavioral psychotherapy. The effect of long-term, psychoanalytic treatment has not been assessed so far. In this study (Buchheim et al. 2012, PLoS One 7:e33745) recurrently depressed (DSM-IV) unmedicated outpatients (n= 16) and control participants matched for sex, age, and education (n= 17) were investigated for the first time before and after 15 months of psychoanalytic psychotherapy. Participants were assessed with the Adult Attachment Projective Picture System (AAP) to evaluate attachment representations. Moreover participants were scanned at two time points, presenting AAP pictures combined with personalized core sentences previously extracted from the AAP interviews, contrasted with non-personalized, neutral descriptions of the AAP pictures. Patients showed a higher percentage of disorganized attachment representations at the beginning of treatment compared to controls and these disorganized patterns changed to organized patterns after 15 months. Patients showed a higher activation in the left anterior hippocampus/amygdala, subgenual cingulate and medial prefrontal cortex before treatment and a reduction in these areas after 15 months. This reduction was associated with improvement in depressiveness specifically and in the medial prefrontal cortex with symptom improvement more generally (Buchheim et al. 2012, PLoS One 7:e33745).